2018
DOI: 10.1103/physreva.98.013628
|View full text |Cite
|
Sign up to set email alerts
|

Topological invariants in dissipative extensions of the Su-Schrieffer-Heeger model

Abstract: We investigate dissipative extensions of the Su-Schrieffer-Heeger model with regard to different approaches of modeling dissipation. In doing so, we use two distinct frameworks to describe the gain and loss of particles, one uses Lindblad operators within the scope of Lindblad master equations, the other uses complex potentials as an effective description of dissipation. The reservoirs are chosen in such a way that the non-Hermitian complex potentials are PT -symmetric. From the effective theory we extract a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 42 publications
0
61
0
Order By: Relevance
“…One can similarly show that the same holds for the case of pure gain and for separate loss and gain channels on each site. The authors of [36] found a similar result for a dissipative SSH model, in which the topological band structure of the Liouvillian was identical to that of the Hamiltonian.…”
Section: Topological Properties Of X(k)mentioning
confidence: 60%
“…One can similarly show that the same holds for the case of pure gain and for separate loss and gain channels on each site. The authors of [36] found a similar result for a dissipative SSH model, in which the topological band structure of the Liouvillian was identical to that of the Hamiltonian.…”
Section: Topological Properties Of X(k)mentioning
confidence: 60%
“…We note that Berry phases for non-Hermitian systems are defined in several contexts [129,130]. However, it remains unsolved whether there exists a topological invariant that characterizes the topological properties even in the presence of the jump term.…”
Section: B Properties Of the Berry Phase χ Knmentioning
confidence: 97%
“…In Fig. 2, we present two examples of the winding numbers (ν 0 , ν π ) versus the imaginary parts of hopping amplitudes v 1 = v 2 = v in our PQL model (25). In both cases, we observe that the topological invariants ν 0 (solid line) and ν π (dashed line) and their changes are consistent with the mean chiral displacements C 0 (circles) and C π (triangles), respectively (see Appendix A for the definitions of C 0,π ).…”
Section: Non-hermitian Floquet Topological Phases In a Pqlmentioning
confidence: 99%